Sky-High Transformation: Measuring Tourist Satisfaction in Ahmad Yani Airport’s New Era - MAULIDHIYA, Adisti; PRANOTO, Pranoto (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the level of tourist satisfaction regarding the change in status of Jenderal Ahmad Yani Airport from an international to a domestic airport, as stipulated in the Decree of the Minister Nomor KM 31 Tahun 2024. This change affects the airport's classification, including the elimination of direct flight routes to Singapore and Malaysia. To evaluate the level of tourist satisfaction, the study employs the Customer Satisfaction Index (CSI) method with a questionnaire that assesses various aspects of service, such as accessibility, check-in processes, security checks, and terminal facilities. The sample consists of passengers who have used the airport's services in the past year, using a purposive sampling technique. The data is analyzed statistically using instrument tests, classical assumption tests, and multiple linear regression. The results indicate that service quality and connectivity have a significant effect on tourist satisfaction. The change in the airport's status also impacts passenger traffic for tourism purposes. Prior to this change, the airport served international routes that supported visits from foreign tourists to Central Java. However, with the loss of direct international routes, international tourists must now transit at other airports such as Jakarta or Surabaya, which increases travel costs and time. Nevertheless, this change opens up opportunities to increase the number of domestic passengers, contributing to the growth of local tourism. Therefore, evaluating the need for new infrastructure and improving service quality are priorities to ensure the sustainable growth of the tourism sector.